SPECIFIC FEATURES OF ATTRACTING INVESTMENTS IN HUMAN CAPITAL IN ECONOMICALLY DEVELOPED COUNTRIES - PhD Akhmadaliyeva Nikhola (European Science Publishing, 2025)
This article explores the experiences of Singapore and South Korea, both of which have successfully integrated education and health policies to build a productive, healthy, and innovative workforce. Singapore's comprehensive educational reforms and healthcare system, alongside South Korea's focus on aligning education with labor market needs and fostering innovation, are analyzed as models for other countries, including Uzbekistan.
Keywords: Human Capital, Investment in Education, Investment in Healthcare, Economic Development, Singapore, South Korea, Uzbekistan, Human Capital Index, Educational Policy, Health Policy, Innovation, Sustainable Growth.